Colonial heritage in Latin America: damnatio memoriae or transcultural dialogue? - Polónia, A.; Costa, C. M. (Preserving transcultural heritage: your way or my way?, 2018)
How the past is appropriated by contemporary actors is subject to multiple dynamics, involving different stakeholders and contested interpretations. The emergence of a heritage industry adds a variety of actors to the debate, including decision-makers, archaeologists, social and cultural academics, business people and entrepreneurs, each one with a different perspective (Falser and Juneja, 2013, p. 1). More recently, local communities were added to these debates as some projects involving heritage sites were contested or even failed altogether. A considerable part of the heritage projects were associated with touristic plans and imposed massive numbers of visitors to some places seen as essential to the identities of such local communities, at times disregarding their memories, symbolic meanings or past interpretations. Some authors have pointed out diverse issues around colonial heritage, mainly seen as the aftermath of a colonial system (Stoler 2013, p. 2). Discourses based on colonial perspectives, and the fact that some institutions and material heritage are still associated with oppression and foreign domination, (McAtackney and Palmer 2016, p. 473) exacerbate this process. The result is a difficult assimilation of some sites or components of that heritage by today’s communities, calling for the recognition of autochthone identities and values. One of the reasons for refusing to accept this heritage is that the concept of keeping and preserving is rather different from the western concept of heritage preservation. The former includes, e.g., the invasion of heritage sites by nature (e.g., forest overgrowing built-upareas), that can be accepted as a natural ending of a built patrimony which lost its functions and makes room for new practical uses, including recovering the uses of that territory in pre-colonial times (Luco 2013, p. 256).